The Physiological Responses of Zea Mays L. and Cucumis Sativus L. on Drought Stress and Re-Watering - Selis Meriem; Evi Muliyah; Melisnawati H. Angio; Triadiati Triadiati (Jurnal Biodjati, 2021)
Drought leads to deficit water availability and its detrimental effects seriously threaten plant growth. This study assessed the physiological, biochemical, and antioxidant adjustments in different types of photosynthetic plants between Zea mays L. (C4) and Cucumis sativus L. (C3 plant) under response to short-term drought stress. Analyses of relative water content (RWC), proline, and ascorbic acid (AsA) were performed to explore how these plants react to drought. Fifteen-day-old plants were subjected to full irrigation or gradual drought periods for 2-d, 4-d, 6-d, and 8-d following by recovery for 7-d. The results revealed that drought significantly reduces leaf RCW in both plants. Re-watered Z. mays after 8-d drought was higher than C. sativus and reestablished RCW by 23% of stressed plant although remained lower by 9% of the well-watered plant. While, proline and AsA contents in Z. mays were higher than those in C. sativus in drought treatment at 8-d (2.05 Âµmol/g FW) and 6-d (3174.60 AsA/100 g FW), respectively, that could demonstrate osmotic adjustment ability in this C4 species. The increased proline in both plants also indicates a good strategy for plants to recover. Rewatering gave a decrease AsA and could be expected that plants restore cellular activity after oxidative injury. Based on our study, proline is the most informative biochemical marker to differentiate plant response to drought and Z. mays adjusted defense mechanism to drought rather than C. sativus due to higher accumulation of proline, better antioxidant activity, and improved RCW after recovery.